A comprehensive overview of the current fisheries status in Sierra Leone - Samuel Julius Kargbo; Noora Barzkar; Dellarose Yuletide Cole; Kenneth D. Kamara; Akshatha Soratur; Rafidah Othman; Olga Babich; Stanislav Sukhikh; Balu Alagar Venmathi Maran (African Science Publications, 2024)
Sierra Leone's fishing sector, rich in seafood stocks such as pelagics, demersals, crustaceans, sharks, and rays, plays a vital role in the nation's economy and food security. Supported by the nutrient-rich Guinea Current Large Marine Ecosystem (GCLME) and the Canary Current Large Marine Ecosystem (CCLME), these resources sustain both industrial and artisanal fisheries. Artisanal fisheries, divided into aquaculture and inland and marine categories, contribute significantly, with fish accounting for approximately 80% of the animal protein consumed daily by Sierra Leoneans. Despite its potential, the sector is hindered by inadequate management, infrastructure, and investment in advanced technology, leading to stagnation over the past 30 years. The artisanal fleet is poised for growth if restrictive measures are not implemented, due to insufficient effort control. Unlicensed fishing and a lack of scientific and technological advancement among local fishermen exacerbate these challenges, threatening food security and economic growth. Effective management strategies are crucial, necessitating thorough independent stock assessments and robust guidelines to address ungoverned and illegal fishing activities. Institutions for marketing, certifying resource ownership, and supplying inputs are also needed. Highlighting the importance of small pelagic species like mackerels, Bongo, Lati, and Herring, the Ministry has proposed specific management strategies aimed at restoring fisheries and the environment. By addressing these issues, Sierra Leone can unlock the fishing sector's potential to alleviate poverty and drive economic advancement. The implementation of comprehensive management measures and investment in technological and infrastructural improvements are essential for ensuring the sector's sustainable growth and contribution to the nation's development.